PERFORMANCE OF EMPLOYEES OF THE AGRO JAYA PALM OIL PLANTATION COOPERATIVE IN LALANG VILLAGE, TAYAN HILIR DISTRICT, SANGGAU REGENCY - Cahyadi, Amos; Aritonang, Marisi; Suharyani, Anita (Jurnal Sains Pertanian Equator, 2025)
Agro Jaya oil palm plantation cooperative in Lalang Village, Tayan Hilir District, Sanggau Regency in carrying out its duties and functions as a partnership forum between PT. Mega Sawindo Perkasa and farmers, namely playing a role in increasing the income and welfare of members through long-term credit from the bank. However, over time the Agro Jaya cooperative has several problems that hinder the performance of the cooperative due to the low performance of employees as indicated by the low discipline and transparency of cooperative employees towards information and services to members. The purpose of this study is to analyze the performance of Agro Jaya cooperative employees located in Lalang Village, Tayan Hilir District. The research method used is quantitative descriptive which is analyzed using the Method of Summated Rating (Likert Scale). The level of performance of Agro Jaya cooperative employees is in the moderate category, this indicates that the level of employee work discipline is still lacking, this can be seen from employees who do not implement the established SOPs, employees have not been able to provide satisfactory service to cooperative members and are not on time when coming to work.